2015
DOI: 10.14257/ijt.2015.3.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Road safety in Kuwait: Results from a Recent Survey

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The majority of studies in existence are extremely dated and thus the conclusions that have been drawn from these may by now be significantly changed (Bener and Jadaan, 1990;Bener et al, 2003). AlSaeid et al (2015) carried out an investigation to analyse and investigate characteristics of road users' and drivers on the roads. They reported that journey purpose, mode of travel and regulations are all factors which contribute to road safety and behaviour of drivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies in existence are extremely dated and thus the conclusions that have been drawn from these may by now be significantly changed (Bener and Jadaan, 1990;Bener et al, 2003). AlSaeid et al (2015) carried out an investigation to analyse and investigate characteristics of road users' and drivers on the roads. They reported that journey purpose, mode of travel and regulations are all factors which contribute to road safety and behaviour of drivers.…”
Section: Introductionmentioning
confidence: 99%
“…However, socio economic data and attitudes were not possible to investigate. AlSaeid et al (2015) investigated characteristics and travel behaviour data for work travellers in Kuwait. The current paper presents a further insight into the analysis of the attitudes and behaviour of work travellers in Kuwait and an investigation of their perception towards traffic safety.…”
Section: Introductionmentioning
confidence: 99%